Molecular epidemiology of the thalassaemias (including haemoglobin E). - Hill, A (1992)
The thalassaemias are the most common genetic disorders of man, and over the last decade the molecular epidemiology of these defects has been studied in detail. After briefly reviewing the great diversity of mutations giving rise to these conditions, four global regions are discussed in more detail. The thalassaemias, of which haemoglobin E is one, are most frequent in Asia, where recent work has defined the molecular basis of the beta thalassaemias and the frequencies of the various types of alpha + and alpha 0 thalassaemia. Oceanic populations have a range of globin gene variants remarkably different to those of south-east Asia. Most is known about the nature and frequencies of thalassaemia mutations in Mediterranean countries, where prenatal diagnosis programmes have been very successful in reducing the frequency of new cases of thalassaemia major. alpha + Thalassaemia is the most common haemoglobinopathy in sub-Saharan Africa, and molecular studies of American Blacks with beta thalassaemia have elucidated the probable molecular basis of the mild form of this disorder in Africans. Although each geographical region has its own group of common beta thalassaemia mutations, with little overlap, most of these appear to have had a single origin. The question of single or multiple origins for HbE in south-east Asia is unresolved. Recombination events producing alpha + thalassaemia deletions are frequent, whereas alpha 0 thalassaemia is produced by a variety of large deletions, each of which has had a single origin. The evidence favouring natural selection by P. falciparum malaria as the primary cause of high frequencies of the thalassaemias throughout the tropics and subtropics is reviewed. While the mechanism of protection remains unclear, epidemiological evidence supporting the hypothesis is strong, but more information is required from case-control studies on the amount of protection provided by the various thalassaemia genotypes.